PENINGKATAN KREATIVITAS, BERPIKIR KRITIS, DAN KETERAMPILAN MENULIS CERPEN SISWA SMA IT YABIS BONTANG MELALUI PENDEKATAN PROSES - Helvika Desmilianti; Yusak Hudiyono; Bibit Suhatmady (Bajang Institute, 2025)
This classroom action research was conducted due to the discovery of problems in writing instruction that were not optimal. especially on the quality of student learning, activeness in learning, and the development of student cognitive skills (critical thinking and creativity). This research was to improve short story writing skills, student activeness in learning, and critical thinking skills and creativity of class XI students of SMA IT YABIS Bontang in the 2024/2025 Academic Year through the application of the Process Approach. The subjects of the study were 30 class XI students of SMA IT YABIS Bontang. Data collection techniques were carried out by giving assignments to make short stories, observations, interviews, and questionnaires. The implementation of the research started from the initial survey, cycle I to cycle II. Each cycle consists of (1) planning; (2) implementation of actions; (3) observation; and (4) analysis and reflection. The results of the study showed a significant increase in the three aspects observed. Students' short story writing skills increased from 23% of students who passed the pre-action to 90% of students who achieved a score of ≥ 75 in cycle II. Student activity during learning also increased in each cycle, including activity during apperception (from 35% to 83%), attention to the material (from 40% to 87%), activeness in asking/responding (from 27% to 67%), cooperation and discussion (from 15% to 87%), and seriousness in doing assignments (from 55% to 90%). Furthermore, the implementation of the Process Approach has also been proven to improve students' critical thinking skills, marked by a shift in the majority of students from a low level (86.66%) in cycle I to a high level (76.66%) in cycle II. Likewise, students' creativity in writing short stories increased, with the majority of students moving from a moderate level (63.33%) in cycle I to a high level (70%) in cycle II, and most even reached a very high level (33.33%). This finding indicates that the application of the Process Approach is effective in improving students' short story writing skills, learning activity, and critical thinking skills and creativity